Double spiral amphorae inscribed with sigla: cases from burial contexts of the Etruscan, Faliscan and Latium area (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2020)
L’anfora a doppia spirale è considerata indicatore rilevante per l’età orientalizzante nell’area etrusca, laziale e falisca. In questo vasto repertorio da contesti funebri si contano alcuni esemplari che hanno restituito sigla. Nel contributo si offre un catalogo degli esemplari e uno studio dei sigla apposti secondo il protocollo dell’International Etruscan Sigla Project (IESP), analizzandone anche l’impaginato e le associazioni di motivi ricorrenti. The amphora decorated with a double spiral is currently considered a reliable indicator of the orientalising culture in Etruria, Latium, and in the Faliscan area. A good number of amphoras, within a vast repertory of funerary equipment, bear sigla. This contribution offers a catalogue of all specimens and a study of all their sigla, according to the International Etruscan Sigla Project (IESP). It analyses their layout and associations of recurring motifs.
Keywords: Etruscan amphoras decorated with a double spiral; orientalising period; funerary context; International Etruscan Sigla Project (IESP); alphabetiform sigla; pentaculum